The Influence of Leadership on the Work Morale of Members in the Organization of the Muhammadiyah Student Association of Banggai Regency - Aji Purnama, Wahyu (Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the influence of leadership on the morale of members in the organization of the Muhammadiyah Student Association (IMM) of Banggai Regency. The global problem in this study is the importance of effective leadership in maintaining and improving the morale of organizational members, which is a key element in operational success. With a descriptive quantitative approach, data was collected through a survey using a questionnaire distributed to 100 respondents who were active members of IMM. Saturation sampling techniques are used to ensure the entire population is represented. The results of the study show that leadership has a significant influence on the work morale of members. A simple linear regression analysis yielded the equation Y=7.234+0.626(X)+eY = 7.234 + 0.626(X) + eY=7.234+0.626(X)+e, where the leadership variable contributed 35.4% to the morale of the members, based on an Adjusted R Square value of 0.354. The results of the correlation test showed a coefficient of 0.600 (60%), which showed a strong relationship between leadership and work morale. These findings indicate that effective leadership can create high motivation and improve member performance. The conclusion of this study is that the role of good leadership is an important factor in increasing the morale of IMM members of Banggai Regency. This research provides practical implications for organizational managers to optimize leadership styles as an effort to improve members' motivation and performance on an ongoing basis. The results of the research also contribute academically in understanding the relationship between leadership and work spirit in student organizations.